MALDI-TOF: Introduction in routine of a system for the rapid identification of microorganisms - Chiara Vismara (Microbiologia Medica, 2011)
Introduction. MALDI-TOF (Matrix Assisted Laser Desorption/Ionization-Time of Flight) is an recently introduced technique for the rapid identification of microorganisms by mass spectrometry (1,3) (Fig.1).The aim of this work was the evaluation and validation of the MALDI-TOF method (Bruker Daltonics) for inclusion in the routine workflow of a clinical microbiology laboratory. Methods.We analyzed strains isolated from different clinical specimens. For each species of microorganism we calculated the percentage of agreement by comparing the identification of MALDI-TOF with that obtained using the methods currently in use in the laboratory. In case of discordant results the conclusive identification was carried out by sequencing of 16S ribosomal DNA (Tab.3) using the MicroSeq identification system 500 (Applied Biosystems) (2). Alpha-hemolytic streptococci were instead identified by the ATB galleries (BioMerieux).ATCC strains were used as Quality Control. Results. 1340 strains were analyzed, including 479 enterobacteria, 188 gram-negative bacilli, 189 staphylococci, 140 enterococci, 84 Haemophilus spp, 114 streptococci, 40 yeasts and 106 less common microorganisms. Gramnegative bacteria, enterococci, Staphylococcus aureus, beta-hemolytic streptococci and yeasts showed full agreement (Tab.1 e Tab.2). In addition, MALDI-TOF has proved a reliable method for identification of fastidious germs such as Legionella, Branhamella, Neisseriae, Listeria monocytogenes, Corynebacteria, and anaerobes.Alpha-hemolytic streptococci were but in most cases identified as S. pneumoniae. Conclusions. The identification by mass spectrometry allows to obtain reliable results in minutes for most of the organisms isolated from the routine. Considerable importance for the performance of the system plays the quality of the database in the instrument. The high percentage of concordance between identification with the standard methods and MALDI-TOF allowed the introduction of this method in routine workflow with the exception of alpha hemolytic streptococci for which the current system of identification is still in use.